Rondo Capricco - Lemare, Edwin H. (Edwin Henry), 1865-1934.; St. Clair, Floyd J., 1871-1941.; State Theatre (Sydney, N.S.W.) (1900)
Part of the State Theatre collection of cinema scores and parts, mainly used for silent movies, but including musical materials associated with talking pictures ca. 1900-1950, used by the State Theatre and various film distribution companies throughout Australia. Some items include performance annotations.
Stamped: Union Theatres Ltd ; Haymarket Theatres Limited.
The music is in an annotated folder that shows lending date, place or name of cinema.
The stamped marking on the material indicates the film distribution companies or theatres that owned, used, or distributed the music to other cinemas.
Keywords: Dramatic music; Instrumental music -- Scores and parts; Silent film music